Translation Analysis of Body-Related Metaphors in the Holy Koran by: Yusuf Ali, Marmaduke Pickthal and Thomas Irving - Seyyed Ali Keshvari (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2017)
The present study is a Corpus-based research which analyzes the translation of Body-Related Metaphors in the Holy Koran by Yusuf Ali, Marmaduke Pickthal and Thomas Irving, within the framework of Peter Newmark’s procedures of metaphor translation. The data analyzed consists of a sample of 107 words and phrases which are categorized as: metaphors of ear, eye, face, and hand. Out of the seven procedures proposed by Newmark for translating metaphors, the translators applied five procedures. None of the translators applied Newmark’s fourth or sixth procedure and no new procedure was observed. The results reveal that among 107 metaphors examined, there is a general tendency (57.94%) towards reproducing the same image in the TL, and the three translators translated 68 metaphors (63.55%) using similar procedures. This study concludes that the likely and the most frequent metaphor translation procedures in the Holy Koran are: (1), to reproduce the same image in the TL, Newmark’s first procedure; and (2), to convert metaphor to sense (literal meaning), Newmark’s fifth procedure.